Pengaruh Tata Ruang Kantor Terhadap Produktivitas Kerja Karyawan Pada PT. Bank Sumut KC. Syariah Medan - Audrey Carissa Br. Sipahutar; Albara Albara (Yayasan Rahmat Islamiyah, 2021)
As for the results of this study, spatial planning has a significant effect on employee productivity at Bank Sumut Syariah Kc Medan as seen from t count > t table (4.441> 2.048) and a smaller significance level of 0.05 (0.000 <0.05), and determination of 41.3% the contribution of office layout to productivity in this study, while the remaining 58.7% was influenced by other factors not examined in this study.